An Investigation of the Performance of Stone Mastic Asphalt Mixture Subjected to Ageing (Sebha University Conference Proceedings, 2024)
One crucial element of the infrastructure designed by civil engineers is the highway. Stone Mastic Asphalt (SMA) is a recently developed asphalt mix that is characterized by a high amount of coarse aggregate, filler, and asphalt, setting it apart from regular dense asphalt. As fillers, 6% calcium carbonate and 2% ordinary Portland cement (OPC) were added to the coarse-graded mix to prevent stripping and reduce binder drain down. The high coarse aggregate structure contributes to the creation of a stable matrix, improving its resistance to long-term deformation. This study's primary goal is to look at how varied ageing times and temperatures affect the performance of SMA mixtures. This study includes abrasion loss, permeability, and skid resistance performance tests. Utilizing a one-way ANOVA, results were examined. The findings indicate that there is no statistically significant relationship between age and skid resistance or abrasion loss. Meanwhile, the resilient modulus and skin temperature differential are statistically significantly impacted by the length of ageing. The combination thoroughly waterproofs the pavement and shows improved resistance to rutting due to its impermeable pavement.